High Frequency of Natural Genetic Transformation of Pseudomonas stutzeri in Soil Extract Supplemented with a Carbon/Energy and Phosphorus Source - Lorenz, Michael G. (1991)
Agar medium (SME) prepared from aqueous soil extract was used to examine genetic transformation of Pseudomonas stutzeri JM302 (his-1) by homologous his(+) DNA in a plate transformation assay. Growth studies indicated that SME was strongly limited in carbon and nitrogen sources. Transformation was observed on SME supplemented with pyruvate, phosphate, and ammonium. A 25-fold increase of the transformation frequency was obtained with nitrogen limitation when SME was supplemented with only pyruvate plus phosphate. Similar results were obtained with artificial soil extract medium prepared on the basis of the chemical analysis of the soil extract. On a standard minimal medium, transformation frequencies also increased (10- to 60-fold) when ammonium, phosphate, or pyruvate was growth limiting. Limitation of two or three nutrients did not stimulate transformation. The size of the inoculum (2 × 10(3) to 2 × 10(7) cells) was irrelevant to the enhanced transformation under nitrogen limitation on SME or standard minimal medium. We further show that P. stutzeri can use a variety of carbon and energy sources for competence development. It is concluded that genetic transformation of P. stutzeri is possible in the chemical environment of soil upon supply of nutrients and may be strongly stimulated by a growth-limiting concentration of single nutrients including sources of C, N, or P.